ЗНАЧЕНИЕ НАРОДНЫХ ТРАДИЦИЙ В ТРУДОВОМ ВОСПИТАНИИ - Дошниязов, Ж.К. (SCIENCE and SOCIETY, 2025)
The article analyzes the attitude of folk pedagogical wisdom in folk pedagogy to folk traditions, customs, folklore of adults and children, folk holidays, proverbs, songs, jokes, sayings, epics and legends on various topics, labor relations in the family and society.
Keywords: pedagogy; folk pedagogy; nationality; customs; traditions; children's folklore; education; diligence; labor education; proverbs; heritage; art; culture; epics